Pemberdayaan UMKM Melalui Media Digitalisasi Bisnis Modern dalam Peningkatan Kinerja UMKM di Desa SIDOREJO - Vicky Indarto Setyono; M. Yogi Saputra; Isna Ayu Safitri Kusuma Dewi (Fakultas Teknik Universitas Maritim AMNI Semarang, 2022)
Today's technology continues to grow and the benefits of using the internet are felt for the users. Some people feel dependent on the internet, including the activities of Micro, Small and Medium Enterprises (MSMEs) in utilizing information technology to run their business, especially in the era of the ASEAN Economic Community (AEC). The purpose of this study is to generally describe the impact of digital marketing on sales volume for MSMEs in Sidorejo village. This research is of a qualitative type, using a triangulation model, which combines structured interview methods, in-depth interviews and observations of MSME actors who are actively registered at the Office of Market Community Empowerment – Cooperatives and City Small and Medium Enterprises. From the research results it is known that digital marketing makes it easier for MSME actors to provide information and interact directly with consumers, expand market share, increase awareness and increase sales for MSME players in Sidorejo village. This program emphasizes the importance of understanding digitization from an early age for Micro, Small and Medium Enterprises (MSMEs) to market products in today's modern business style, and is expected to increase the value branding of these products or increase sales turnover.